Social support perception in parents of children with type 1 diabetes mellitus - Natalia Macarena Maureira MIranda; Claudia Maribel Muñoz Pavez; Maria Cecilia Toffoletto Toffoletto; Ángel Roco Videla (Medisur)
Foundation: the support of family members and the health team for parents caring for their diabetic children is essential for facing with the changes that this disease causes in family dynamics. Objective: to describe the perception of parent caregivers about family support and Health Systems at the beginning of their children with type 1 diabetes mellitus. Methods: qualitative descriptive study carried out through semi-structured interviews with four parent caregivers of children with a diagnosis of type 1 diabetes. Informed consent was carried out via Google forms and the interview was via the ZOOM platform. The interviews lasted 30 minutes. The analysis of the interviews was carried out using the ATLAS.ti version 22 program. Results: the beginning of the children's illness was received by parents with much confusion and lack of knowledge. Regarding the support networks, the parents declared loneliness in the experience of caring for the children and, in relation to the health teams, they reported that it is focused on the basic care that they had to fulfill, such as food and hygiene, glycemic control, with absence of concern for emotional support. Conclusions: the support needs from health teams to parent caregivers, beyond disease control, is an explicit need from the evidence, which has not yet been considered by Health Systems. Support must go beyond the family, with important action by health professionals and the entire context in which children are inserted, to contribute to adequate management of the disease.